IMPROVING STUDENTS' CRITICAL THINKING SKILLS USING THE TPACK-BASED NUMBERED HEAD TOGETHER (NHT) LEARNING MODEL IN HISTORY LEARNING AT STATE SENIOR HIGH SCHOOL 1 BOGOR: MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MENERAPKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBASIS TPACK PADA PEMBELAJARAN SEJARAH DI SMA NEGERI 1 BOGOR - Restu Yanuar Ula; Darsono; Sariyana (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to improve students' critical thinking skills by applying the TPACK-based Numbered Head Together (NHT) learning model in history learning at SMA Negeri 1 Bogor. The research subjects were students of class X-4 at SMA Negeri 1 Bogor. This NHT learning model is applied as a strategy to improve students' critical thinking skills based on TPACK. This research shows that the application of the TPACK-based Numbered Head Together (NHT) learning model has a positive impact on teachers and students. This can be seen in the learning process that teachers are more creative in applying innovative learning models and students look active and motivated and are able to improve their critical thinking skills by analyzing questions in the student worksheet (LKPD) given in the learning process. Thus it can be concluded that the application of the TPACK-based Numbered Head Together (NHT) learning model can increase teacher creativity, increase critical thinking skills and student motivation.